2016
DOI: 10.1080/00365521.2016.1195870
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and quality of care in IBD

Abstract: Predictors for non-adherence were young age and smoking. High adherence rates could be explained by a high patient satisfaction and a high degree of shared decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The patient's involvement in the treatment selection led to higher confidence in the selected treatment option (second part of H2). 'The extent to which the patient's behaviour matches agreed recommendations from the prescriber' along with mutual agreement on treatment decisions refer to adherence [49,50]. Thus, involvement in treatment selection leads to higher decision certainty about the treatment, which fosters patient's adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's involvement in the treatment selection led to higher confidence in the selected treatment option (second part of H2). 'The extent to which the patient's behaviour matches agreed recommendations from the prescriber' along with mutual agreement on treatment decisions refer to adherence [49,50]. Thus, involvement in treatment selection leads to higher decision certainty about the treatment, which fosters patient's adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter, prospective cohort study including 1,558 patients with CD and 1,054 patients with UC, younger age at diagnosis, flares, feelings of anxiety or depression, and nonadherence were associated with future nonadherence to treatment [13]. A recent study from Bager et al [2] reported young age and smoking as predictors of nonadherence, while high adherence rates were explained by high patient satisfaction and high degree of shared decision making. A very recent study published by Keil et al [14] conducted in 198 outpatients with a diagnosis of UC has shown that the patient’s education level can significantly influence compliance to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of the disease is symptomatic, and adherence to treatment has an impact on the course of the disease [2]. Medical treatment is required to induce and maintain remission of IBD, and adherence to treatment has been associated with positive treatment outcomes [3-5].…”
Section: Introductionmentioning
confidence: 99%
“…After univariate and multivariate analyses, perception of ease in contacting the gastroenterologist in case of need was a protective factor for inadequate adherence to both oral 5-aminosalicylates and thiopurines. Quality of care and high patient satisfaction have previously been linked with high treatment adherence rates in IBD patients [32]. This finding underscores the importance of IBD nurses in the IBD multidisciplinary team, in which one of their key role is accessible care [33].…”
Section: Discussionmentioning
confidence: 74%